QOLP-22. DRIVERS OF COST OF SURGERY IN NEWLY-DIAGNOSED GLIOBLASTOMA PATIENTS. (11th November 2019) - Chandra, Ankush; Young, Jacob; Dalle-Ore, Cecilia; Lau, Darryl; Rick, Jonathan; Wadhwa, Harsh; McDermott, Mike; Berger, Mitchel; Aghi, Manish
Abstract: INTRODUCTION: Glioblastoma carries a high economic burden for patients and caregivers. We investigated drivers of hospital costs of surgery for newly-diagnosed glioblastoma. METHODS: Retrospective review of GBM patients undergoing first resection at UCSF (2010–2015) and corresponding hospital charges. Our cohort was divided into low (LC) and high cost (HC) groups for total surgical cost. Multivariate regression was used to identify factors driving cost of surgery. RESULTS: Of 242 patients, 36.7% (n=86) were females (median age=62 years). The mean total hospital cost for surgery among our patient cohort was $40, 384. When comparing the LC and HC groups, mean total hospital cost for surgery for HC patients was almost twice as much as LC group ($51, 744 vs $29, 023, p< 0.001). Kaplan-Meier analysis revealed that having higher cost of surgery worsened patient prognosis, with a 21% longer overall survival in the LC cohort versus the HC cohort (14.7 vs 17.9 months, p=0.02; HR=1.41 [1.05–1.91], p= 0.023). Tumor diameter at diagnosis was largest for HC group (4.7 cm) versus LC patients (3.9 cm, p=0.002). Multivariate analysis revealed longer hospital stay (F-ratio=8.87; p=0.01), longer ICU stay (F-ratio= 12.34, p< 0.001), younger age at surgery (F-ratio=6.71, p=0.02) and multifocal disease (F-ratio=6.26, p=0.02) to be independent predictors of higher cost of surgery, while having PCP at diagnosis (F-ratio=6.92, p=0.02), health insurance coverage (F-ratio= 4.23, p=0.03) and being married (F-ratio=3.71, p=0.04) were independent predictors of lower cost of surgery. CONCLUSIONS: Higher costs of surgery correlate with worse survival outcomes in glioblastoma patients. Beyond the anticipated finding that greater disease burden drives some of this inverse correlation between cost and survival, correctable socioeconomic factors such as PCP and insurance status also drive higher hospital charges for GBM surgery. Manipulation of these factors is necessary to minimize the economic burden of disease and adopt cost-effective surgical treatments for GBM patients.